Discretionary Fiscal Policy and Optimal Monetary Policy in a Currency Area - Stefano Gnocchi (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2007)
The paper evaluates the effects of fiscal discretion in a currency area, where a common and independent monetary authority commits to optimally set the union-wide nominal interest rate. National governments implement fiscal policy by choosing government expenditure. The assumption of fiscal policy coordination across countries is retained in order to evaluate the costs exclusively due to discretion, leaving aside the free-riding problems stemming from noncooperation. In such a context, nominal rigidities potentially generate a stabilization role for fiscal policy, in addition to the one of ensuring efficient provision of public goods. However, it is showed that, under discretion, aggregate fiscal policy stance is inefficiently loose and the volatility of government expenditure is higher than optimal. As an implication, the optimal monetary policy rule involves the targeting of union-wide fiscal stance, on top of inflation and output gap. The result questions the welfare enhancing role of government expenditure, as the proper instrument for stabilizing asymmetric shocks. In fact, discretion entails significant welfare costs, the magnitude depending on the stochastic properties of the shocks and, for plausible parameter values, it is not optimal to use fiscal policy as a stabilization tool.
Keywords: 330